Nanocompósitos poliméricos para imageamento não invasivo em tanques de simulação hidráulica - Gonçalves, Raiane Valenti (2013)
The mechanisms of initiation, transport and deposition of sediment in turbidity currents have been studied because of its potential environmental impact and for containing the main hydrocarbon reservoirs. Several research groups have performed simulations of these phenomena in reduced models, using the coal 205 as sediment. However, this material has limitations on its use in noninvasive imaging techniques for monitoring of turbidity currents in tanks of hydraulic simulation. Thus, this study aimed the preparation of polymer nanocomposites with the potential to replace the coal 205 in these simulations. Polymer nanocomposites based on thermosetting matrices containing inorganic filler (clay, graphite and carbon black) were prepared.By means of scanning electron microscopy (SEM) and transmission electron microscopy (TEM) micrographs it was possible to verify that the fillers incorporated into polymer matrices showed nanometric dimensions and were dispersed homogeneously, except the carbon black that presented some points of agglomeration. The forms of particles are also evaluated by SEM , classified as semi-angular and semi-rounded. The electrical properties were investigated using electrical impedance spectroscopy. The materials studied presented values of settling velocities and density near the coal 205. Thus, all nanocomposites prepared exhibited the desired characteristics to replace the coal 205 in tank hydraulics simulation.